PENGARUH DIGITAL MARKETINGTERHADAP ORGANIZATIONAL PERFORMANCE DENGANINTELLECTUAL CAPITAL DAN PERCEIVED QUALITYSEBAGAI VARIABEL INTERVENING PADA INDUSTRI HOTEL BINTANG TIGA DI JAWA TIMUR - Willy Andrian Prabowo (Institute of Research and Community Outreach - Petra Christian University, 2018)
The influence of Digital Marketing on Organizational Performance with Intellectual Capital and Perceived Quality as an intervening variables in Three Star Hospitality Industry in East Java.The growth of tourism in Indonesia is growing abundantly. People’s desire for vacation is developing through the years. This enables intense competiton in the Hospitality Industry in East Java.This research aims to analyze the influece of Digital Marketing (Interactive, Incentive Programs, Site design, Cost), to Organizational Performance in Hotel Industry in East Java with Intellectual Capital (Human Capital, Customer Capital, Structural Capital) and Perceived Quality (Tangibles, Reliability, Responsiveness, Assurance, Empathy), as an intervening variables.This research was conducted by distributing questionnaires to 120 respondents internal employees of Three Star Hotel in East Java. Analytical technique used in technical quantitative analysis with path analysis method